ENHANCING SUSTAINABILITY THROUGH SLUM SETTLEMENT UPGRADING. CASE STUDY OF KAMPUNG MOJO, SURAKARTA. - Fikrian Rafika Dewi; Yenni Yosita br Barus; Findara Illa Nursyifa; Asri Ambar Kinasih; Ardhya Nareswari; Ahmad Sarwadi (Built Environment Studies, 2024)
The redevelopment of Kampung Mojo is one collaborative design project aimed at improving the quality of slum settlement by supporting basic infrastructure and providing housing. This study focuses on three pillars of sustainability: social, economic, and environmental, by exploring the usage of outdoor space following the upgrading process. The objective is to gather insights that cater to the community's needs and foster the realization of sustainable settlement. The method used in this study is qualitative descriptive with data collection techniques through observation and interviews. The findings of this study underscore a diverse array of activities that yield positive implications for raising the sense of communities, creating new economic opportunities, and productive land usage to achieve Sustainability Development Goals (SDGs).